Identification and quantification of phenolic compounds and flavonoids in anthelmintic ethnoveterinary plants used among Fulani and Mosse, Central Burkina Faso - Adama HILOU,; Rappez Florence,; Duez Pierre, (International Journal of Phytomedicine, 2014)
Helminthic diseases are the leading cause of loss of animals in the Sahel region of Western Africa. Poverty, combined with the poor development of modern veterinary services, forces small farmers to use herbals to treat their livestock. A previous ethnoveterinary survey, carried out in the region of Saba in Burkina Faso, indicates a frequent use of the leaves ofAcaciamacrostachyaDC.(Leguminosae), CombretumglutinosumPerr.ex DC. (Combretaceae) and Mitragynainermis (Willd.)Kuntze to treat helminthic diseases. Phytochemical screening has allowed us to characterize sterols, triterpens, flavonoids and tannins as the main phytochemical classesof these 3 species; phenolic compounds range from 2.5 to 8 % and a series of bioactive polyphenols (quercetin, rutin, gallic acid) have been identified by thin-layer chromatography. The obtained results indicate the richness of these herbs in phenolic compounds. The biological activity, toxicology and phytochemistry of the 3 species warrant further investigation to justify their ethnoveterinary uses.